Under the Radiant Sun and the Crescent Moon : Italo Calvino's Storytelling - Jeannet, Angela M. (Book collections on Project MUSE., 2000)
Although Italo Calvino (1923-1985) is one of the most widely read and translated Italian novelists of the century, a comprehensive analytical work in English of his writings has been unavailable until now. In this new study Angela Jeannet offers a rich and vibrant critical portrait that integrates Calvino the creative writer with Calvino the critical thinker, two roles that the novelist himself saw as intimately connected. "Under the Radiant Sun and the Crescent Moon" examines the cultural and literary matrix of Calvino's complex fictional universe, focusing on his passion for storytelling and the various stages in the evolution of his work. Calvino lived in a culture undergoing profound transformations. Jeannet traces the important creative influences and events in his life and their significance for his writing, from his cultivated bourgeois upbringing and reading of the Modernists to his confrontation with post-war industrialism, the consumer culture of the 1960s, and beyond. Throughout the study Jeannet brings to light Calvino's views on the function of storytelling in literature and society and his strong connections to the Italian poetic tradition. She also explores aspects of Calvino's work that deserve more attention, including the critically neglected Marcovaldo stories and the metaphorical role of the feminine in his fictional world.